Revision of Litoria rothii (Anura: Pelodryadidae) from northern Australia - Donnellan, S.c.; Catullo, R.a.; Rowley, J.j.l.; Doughty, P.; Price, L.; Hines, H.b.; Richards, S.j. (Zootaxa, 2023)
Litoria rothii is a widespread pelodryadid frog with a charismatic “laughing” advertisement call, distributed across the Australian Monsoon Tropics and southern New Guinea. Given its large distribution spanning well-known biogeographic barriers, variation in male advertisement calls and the prevalence of unresolved species complexes in the Australian frog fauna, we examine the genetic, morphological and acoustic diversity in the species from across its range. Our analyses reveal the presence of a previously unrecognised species in western parts of the range of L. rothii sensu lato, which we describe herein as a new species. Litoria ridibunda sp. nov. is distinguished from L. rothii on the basis of paraphyly of nuclear gene trees with L. everetti from Indonesia, colour patterns on the posterior thigh and male advertisement calls. Compared to L. rothii, the new species has a less contrasting pattern on the posterior thigh and a male advertisement call with a greater number of notes per call and a greater call duration. In particular, the magnitude of call differences between the species is highest where the ranges of the two species are in proximity in north-western Queensland. Our study further emphasises the undiagnosed diversity that remains in Australian frogs, even in relatively large, charismatic, frequently encountered species that often share human dwellings.